Pencarian Kata Pada Aplikasi Kamus Istilah Komputer dan Informatika Menggunakan Algoritma Brute Force Berbasis Android - Rismayani Rismayani; Novita Sambo Layuk; Sri Wahyuni; Hartana Wali; Ni Kadek Marselina (Komputika : Jurnal Sistem Komputer, 2021)
A computer term dictionary means a dictionary that contains terms with their conceptual meanings from a particular field of science. So far, the term computer dictionary has only been in the form of a physical book and has developed into a digital dictionary in the form of a website or Android-based application available on the Play Store or App store. The problem in this research is that so far there are still many dictionary terms in the form of books. To find the term you want to search, you still have to open a book sheet and search by looking at alphabetical order. This study aims to create an Android-based computer and informatics search dictionary application. The method used is the brute force algorithm method as a method of searching for terms in the application being made, The brute force algorithm is a straight, straight algorithm or it can also be called a plate algorithm. The brute force algorithm is a very complex form of algorithm, because to be able to solve problems with the straight forward or plate technique requires a lot of input and also logical considerations, so that direct problem solving decisions can be obtained. refers to or leads to the desired result. The results of this study are to make it easier for users or users to search for terms quickly and the results of the brute force algorithm can display computer and informatics word search results.